Research and Experiment of Repairable Space Telescope Interface System - Zhen Shi; Weiguo Zhao; Libao Yang; Yang Xun; Qingya Li; Yaoyu Zhang (IEEE Access, 2020)
Space technology is the core competitiveness of a powerful country. Space maintenance technology has just started in our country. The biggest innovation of this article is to design a set of interface system, which is suitable for on-orbit maintenance of space science instruments. It represents that this technology from scratch in our country. A new measuring method is proposed. According to the homogeneous coordinate transformation, the mathematical models of the relationships between fit clearances of interface system and the six-degree of freedom change of the maintenance module are derived. According to the index requirements, the corresponding fit clearance and repeat positioning accuracy are determined. Set up an experimental platform, and use autocollimator and laser tracker to measure the repeated positioning accuracy of the module. Based on the theory of small displacement, the least square method is used to deduce the rotation angle and translation amount of the module through the change of the characteristic point coordinates. The experiment proves that the interface meets the requirement of on-orbit maintainable operation, and the experimental data proves that the theoretical equation is correct. Providing engineering reference for other space maintenance scientific instruments.